The SiCC Column Improved the Expansive Clay - Agus Setyo Muntohar, Siswoko Adi Saputro (Quality in Research, 2015)
In Indonesia, many roads were constructed over the expansive clay that caused road deficiencies as the result of the heaving and shrinking effects of the expansive soil during the seasonal period. Soil improvement using lime and cement is the common method of soil improvement. However, uses of industrial wastes such as carbide and rice husk ash are advantage method to improve the shear strength of expansive soil. This paper is aimed to investigate the compressive strength of the columns of carbide lime/rice husk ash mixtures for improving performance of expansive soil. The carbide lime and rice husk ash was mixed to form a SiCC column in expansive soil. Unconfined compression strength (UCS) test was conducted to establish a general trend for the gain in strength. For the UCS test, the specimen size is 50 mm diameter and 100 mm height and the column size is 0.5 inch diameter. The specimen was compacted in optimum (OMC) and optimum-wet (OW) of compaction. The investigations resulted that the compressive strength of soil-column of carbide lime/rice husk ash mixtures increased with the increasing age of the column from 11 kPa to 127 kPa at 28 days of curing time. At the earlier age, the strength gain of the soil-column prepared at OW side was higher than the soil-column at OMC side. But after 14 days of curing, the strength of soil-column at OMC side is higher than the soil-column at OW side. Thus, the secant modulus of elasticity (E50) of the soil-column at OMC side is generally higher than the soil-column at OW side.